Photo‐Thermal Switching of Individual Plasmonically Activated Spin Crossover Nanoparticle Imaged by Ultrafast Transmission Electron Microscopy. Issue 52 (17th October 2021) - Hu, Yaowei; Picher, Matthieu; Tran, Ngoc Minh; Palluel, Marlène; Stoleriu, Laurentiu; Daro, Nathalie; Mornet, Stephane; Enachescu, Cristian; Freysz, Eric; Banhart, Florian; Chastanet, Guillaume
Abstract: Spin crossover (SCO) is a promising switching phenomenon when implemented in electronic devices as molecules, thin films or nanoparticles. Among the properties modulated along this phenomenon, optically induced mechanical changes are of tremendous importance as they can work as fast light‐induced mechanical switches or allow to investigate and control microstructural strains and fatigability. The development of characterization techniques probing nanoscopic behavior with high spatio‐temporal resolution allows to trigger and visualize such mechanical changes of individual nanoscopic objects. Here, ultrafast transmission electron microscopy (UTEM) is used to precisely probe the length changes of individual switchable nanoparticles induced thermally by nanosecond laser pulses. This allows revealing of the mechanisms of spin switching, leading to the macroscopic expansion of SCO materials. This study is conducted on individual pure SCO nanoparticles and SCO nanoparticles encapsulating gold nanorods that serve for plasmonic heating under laser pulses. Length changes are compared with time‐resolved optical measurements performed on an assembly of these particles. Abstract : An ultrafast electron microscopy study shows how an individual spin crossover nanoparticle, with different number of embedded gold nanorods, acts as an efficient photoswitch where the size of the particle can be controlled within less than 20 ns.